Consumer-based determinants of brand love and its consequences: a quantitative research. (5th July 2019) - Garg, Ruchi; Mukherjee, Jaydeep; Biswas, Soumendu
The objective of the paper is to investigate consumer-based determinants of brand love and its consequences. The study examines brand reputation, brand anthropomorphisation, communal orientation as factors influencing brand love and word of mouth, consumer forgiveness, and willing to pay a price premium as outcomes of brand love. A total of 360 responses were collected and SEM was employed to examine the research model. Findings indicated that brand anthropomorphisation, communal orientation, and brand reputation are indicators of brand love. Results suggested that brand love partially mediated the relation between consumer orientation and consumer forgiveness. Practitioners could employ the research model for consumer segmentation and formulation of their brand positioning and communication strategies. This study could help them in the creation of brand love which further limits the harmful impact of brand failure.